2014
DOI: 10.1002/anie.201310520
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Only Lewis Pairs by Reversible Insertion of Ruthenium and Osmium Fragments into Metal–Boron Double Bonds

Abstract: New metal-only Lewis pairs (MOLPs: Ru→Cr and Os→Cr) are prepared by the insertion of a zerovalent ruthenium or osmium complex into chromium-boron double bonds of borylene complexes. The reaction creates new borylene complexes (the first ever for osmium), and is crystallization-controlled; re-dissolving the complexes results in regeneration of the starting materials. A mechanism is proposed based on DFT calculations, along with a computational study of the unusual MOLPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…The unique robustness and purely σ-donor nature of these M–B linkages (Figure , right) is highly reminiscent of NHC-metal complexes. Indeed, reaction of 2 with the cationic coinage metal species [(IDipp)­CuOTf] results in the formation of the “metal-only Lewis pair” (MOLP) species 6 (Scheme ), Figure ) where a Fe–Cu bond has been formed. This observation stands in contrast to known metalloborylene reactivity with coinage metals, where coordination to the borylene M–B π-bond has been described .…”
Section: Resultsmentioning
confidence: 99%
“…The unique robustness and purely σ-donor nature of these M–B linkages (Figure , right) is highly reminiscent of NHC-metal complexes. Indeed, reaction of 2 with the cationic coinage metal species [(IDipp)­CuOTf] results in the formation of the “metal-only Lewis pair” (MOLP) species 6 (Scheme ), Figure ) where a Fe–Cu bond has been formed. This observation stands in contrast to known metalloborylene reactivity with coinage metals, where coordination to the borylene M–B π-bond has been described .…”
Section: Resultsmentioning
confidence: 99%
“…Der Einsatz eines Nebengruppenmetalls eröffnete also einen Reaktionsweg, der Hauptgruppen‐FLPs verschlossen bleibt. Braunschweig et al berichteten von der Synthese rein metallischer Lewispaare aus Chrom und Osmium oder Ruthenium, die sich durch Borylentransmetallierungsreaktionen und anschließende Kristallisation isolieren lassen (Abbildung 29) 2_36. Das Borylentransferreagenz bleibt im Produkt, so dass die Bildung des Lewis‐Paars reversibel ist: Beim Lösen in Toluol bilden sich die Edukte zurück.…”
Section: Aktivierung Und Funktionalisierung Kleiner Moleküleunclassified
“…Although the mechanism of the conventional borylene transfer reaction has not been definitively determined, a number of bridging dinuclear borylene complexes have been isolated from the process . Indeed, bridging motifs appear to be highly favored with the aminoborylene ligand: BN­(SiMe 3 ) 2 ; thus, the dinuclear, nonbridging borylene MOLP complexes prepared in this earlier report were highly unusual. This MOLP formation was, therefore, presumed to be an offshoot of the conventional borylene transfer mechanism.…”
mentioning
confidence: 91%
“…The MOLP-forming reactions were also found to be reversible, 5 driven in the forward direction by the crystallization of the MOLP−borylene complexes 3a and 3d from hexanes, and in the reverse by dissolution in more polar solvents. This unprecedented phenomenon suggested that the energetic profile of the reaction must be relatively flat.…”
mentioning
confidence: 96%
See 1 more Smart Citation